Pengorganisasian Komunitas Serikat Pekerja Rumah Tangga Sapulidi Dalam Memperjuangkan Situasi Kerja Layak - Ari Ujianto (Brawijaya Journal of Social Science, 2019)
This article discusses community organizing by the Sapulidi Domestic Workers Union Jakarta in fighting for a decent work situation in Indonesia, 2013-2018. The work situation experienced by domestic workers in Indonesia cannot be considered feasible because there is still exploitation, violence, and exclusion from industrial citizenship. One of the reasons for this problem continues to occur, one of which is because domestic workers are not organized. This article aims to elaborate the approach Sapulidi Domestic Workers Union, Jakarta in fighting for a decent work situation. This research used a qualitative approach, with data collection conducted by direct interviews with board and community organizers of Sapulidi Domestic Workers Union, and using documents owned by Sapulidi and other institutions. This research found that with the right organizing strategy, there was a rapid increase in the number of organizational members. In addition, there is also an increase in members' understanding of decent work situations for domestic workers, so that they jointly and individually try to fight for these decent work situations. This study concludes that the struggle in achieving the goals of an organization requires an appropriate and sustainable organizational approach.Keywords: community organizing, domestic workers, decent work